1989
DOI: 10.1111/j.1471-0528.1989.tb06309.x
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen‐induced regression in low‐grade endometrial stromal sarcoma. Case report and literature review

Abstract: A 42-year-old nulliparous woman presented with a large pelvic mass. Laparotomy showed a 20-cm partially cystic lesion suspended in the omcntum, as well as a smallcr solid mass in the rcctovaginal spacc with a protrusion into the pouch of Douglas. The cystic lesion was excised. The ovarics appeared normal and were conserved. Removal of thc lesion in the rectovaginal spacc was delayed until six wccks later, after the histology had been reviewed. This mass was shelled out easily and the capsule left intact.Thc pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
(4 reference statements)
0
8
0
1
Order By: Relevance
“…7, score 12). PR, peroxidase-antiperoxidase, original magnification × 200 Krumholz et al, 1973;Gloor et al, 1982;Baker et al, 1984;Tsukamoto et al, 1985;Keen and Philip, 1989;Montag and Manart, 1989;Rad and Lowe, 1990;Horowitz et al, 1996). Scribiner and Walker (1998) reported preoperative treatment of LGSS with progestins.…”
Section: Discussionmentioning
confidence: 99%
“…7, score 12). PR, peroxidase-antiperoxidase, original magnification × 200 Krumholz et al, 1973;Gloor et al, 1982;Baker et al, 1984;Tsukamoto et al, 1985;Keen and Philip, 1989;Montag and Manart, 1989;Rad and Lowe, 1990;Horowitz et al, 1996). Scribiner and Walker (1998) reported preoperative treatment of LGSS with progestins.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine smooth muscle tumors are also positive for smooth muscle markers and sex steroid receptors (7), but sex steroid receptor expression is often decreased in both high-grade ESSs and leiomyosarcomas (6,7). Such diverse differentiation sometimes leads to diagnostic difficulties among uterine sarcomas, and because progestin treatment is often clinically effective for patients with ESS (8,9), there is a need to find an effective way of differentiating ESS from leiomyosarcoma and other uterine mesenchymal tumors.…”
mentioning
confidence: 96%
“…21 Studies have revealed that therapy with progestational agents is an important adjunct to surgical treatment in cases of lowgrade ESSs. 12,16,18,22 Recurrent or metastatic low-grade ESSs have been reported to be stabilized or suppressed with progestational agents in more than 50% of patients. 16,18,22 However, although most of low-grade ESSs have been shown to express ER and PR, a significant amount of the tumors, even with high ER and PR content, do not respond to adjuvant hormonal treatment.…”
mentioning
confidence: 99%
“…12,16,18,22 Recurrent or metastatic low-grade ESSs have been reported to be stabilized or suppressed with progestational agents in more than 50% of patients. 16,18,22 However, although most of low-grade ESSs have been shown to express ER and PR, a significant amount of the tumors, even with high ER and PR content, do not respond to adjuvant hormonal treatment. 18,22 Epidermal growth factor receptor (EGFR), also known as HER-1, is characteristically expressed in normal endometrial stromal cells.…”
mentioning
confidence: 99%